Effectiveness of linking vegetable farmers to formal markets in Lagos State, Nigeria - Akinwale, Jonathan Akinsola; Oyeyemi, Olamide Victoria (Journal of Agriculture and Natural Resources, 2021)
The study assessed how smallholder vegetable farmers are linked to formal markets in Lagos state, Nigeria. The study specifically described the socioeconomic characteristics of the smallholder vegetable farmers, ascertained perceived benefits from the linkage and constraints in linking smallholder vegetable farmers to formal markets. A random sampling technique was used to sample 120 vegetable farmers from Agbowa and Epe clusters. Data were analysed using descriptive statistics and correlation analysis. The results revealed that smallholder vegetable farmers were relatively young with mean age of 41.5 years, mean household size was 4 persons and they mainly sourced information from friends and fellow farmers. The findings also revealed that the smallholder vegetable farmers had strong linkage with input suppliers (x̅ = 2.50), International Fertilizer Development Center (x̅ = 2.33), World Vegetable Center (x̅ = 1.51) and Center for Inclusive Agriculture and Gender Development (x̅ = 1.46). Exposure to production technologies and specialized training (x̅ = 4.69) were the most perceived benefits from the linkage. Level of linkage with farmers and other actors was constrained by lack of basic infrastructure (x̅ = 2.50) and inadequate credit facilities (x̅ = 2.06). The study also found a significant correlation between household size and level of linkages. The linkages arising from the arrangement had no doubt exposed the farmers to production technologies and market information. Extension agencies and relevant non-governmental organisations are implored to offer specific trainings to vegetable farmers on value addition to enhance their participation in the formal markets.